PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP MOTIVASI BELAJAR IPA DI KELAS IV SDN KELAPA DUA 06 PAGI JAKARTA BARAT - Hakim, Syifa Aulia; Syofyan, Harlinda (International Journal of Elementary Education, 2017)
This study aims to determine the effect of implementation of cooperative learning model type teams games tournament (TGT) in science learning to motivation to learn fourth grade students of SDN Kelapa Dua 06 Pagi West Jakarta. The population in this research amounting to 52 people. The sample of this research consists of two groups, namely the experimental group of 26 people and the trial group of 27 people. Sampling is determined by purposive sampling technique. The results showed that: (1) the observation result during the study showed that the percentage of student activity increased by 66.67% to 93%; (2) t-test results obtained p-value of 0.02 (p <0.05) and tcount> ttable ie 2.42> 2.05 which means reject H0. This shows that there is a positive influence of cooperative learning model of type teams games tournament (TGT) on the motivation to learn science of grade 4 students of SDN Kelapa Dua 06 Pagi Jakarta in the academic year 2016-2017